Randomized control trial of low dose oral misoprostol compared with intracervical dinoprostone gel for cervical ripening - D. R., Savithri; Chennupalli, Prashanthi; R., Suvarna; S., Akshatha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Induction of labour is a therapeutic option when the benefits of delivery outweigh risks of continuing pregnancy. There are several agents for induction of labour to achieve better outcome of labour. Acceptable methods for induction are oxytocin infusion, dinoprostone gel, misoprostol and mechanical cervical dilators. Prostaglandins are the preferred choice in unripened cervix. Objective of this study was to compare efficacy, safety of low dose oral misoprostol compared with intracervical dinoprostone gel for cervical ripening. Methods: One hundred women with single live fetus, term gestation, cephalic presentation, reactive fetal heart pattern and Bishops score <6 were included in the study. They were randomized to receive either 6 doses of 25ug oral misoprostol every 3rd hourly or 0.5ug intracervical dinoprostone every 6th hourly for a maximum of 3 doses. Results: Bishops score improvement after 6,12,18 hours in both the groups was statistically insignificant. Induction delivery interval was11.96±5.88 for misoprostol and 10.95±4.58 in dinoprostone group with P value 0.341 which was statistically insignificant. Need for oxytocin augmentation was less (18%) in misoprostol group as compared to dinoprostone group (44%). Caesarean section rate was slightly higher in misoprostol group (26% vs 24%). Meconium stained amniotic fluid was high in misoprostol group (16%) compared to dinoprostone group (8%). Maternal complications were minimal and neonatal outcome was good in both the groups. Conclusions: Compared to dinoprostone; misoprostol is easy to store, cost effective, stable at room temperature, can be easily administered and had better patient compliance and acceptability. It was found to be a better cervical ripening agent with similar maternal and fetal safety profile.